Playing Pretend or Playing the Part: Enacting Marriage and the Figure of the Bride in Euripides’ Andromache - Foxley, Florencia (2024)
The scope of the Athenian wedding somewhat ambiguous—it is difficult for modern scholars of Athenian ritual, history, and gender studies to agree exactly what constituted the wedding from beginning to end. This article analyzes the gesture, speech, and costuming of two potential brides in Euripides’ Andromache in order to argue that while the wedding comprised many important steps and actions, the central purpose and concluding event for that ritual was the birth of a child. Both Hermione and Andromache enact important bridal behaviors and gestures; however, Hermione, the “legitimate” partner, is associated with the early stages and representations of the wedding, while Andromache, through the physical presence of her child on stage, embodies the completed ritual. The play ends by affirming Andromache’s interpretation of her connection to Neoptolemus and thus supports a definition of a wedding as a ritual that concludes only with the birth of a child.